Food consumption among income classes and its response to changes in income distribution in rural China. Issue 3 (30th July 2018) - Ren, Yanjun; Zhang, Yanjie; Loy, Jens-Peter; Glauben, Thomas
Abstract : Purpose: Given the fact that the income disparity has become extremely severe in rural China, the purpose of this paper is to examine heterogeneity in food consumption among various income classes and to investigate the impact of changes in income distribution patterns on food demand in rural China. Design/methodology/approach: In this study, the authors partition the households into five income classes according to the distribution of household per capita net income. Using household data drawn from the China Health and Nutrition Survey in 2011, a two-stage demand model is applied to estimate a food demand system for each of the income classes. After obtaining the estimated income elasticities of eight studied food groups for each income class, the authors then examine the responsiveness of food demand to the changes in income distribution by means of four scenarios with varying income distribution. Findings: The empirical results indicate that substantial differences in food consumption exist across various income classes. Specifically, the lowest-income households are more sensitive to price and income changes for most studied food groups than the highest-income households are. In general, income responsiveness is higher for meats, aquatic products and dairy products. Based on estimated income elasticities, the projected food consumption under different income distribution patterns shows that changes in income distribution have significant influences on food consumption. In addition, the authors conclude that a more equal distribution of income would be associated with a higher demand for food in rural China. Originality/value: This paper employs a two-stage demand model to estimate food demand in rural China by income classes. The results imply substantial differences in food demand for various income classes. Therefore, income distribution should be taken into account instead of an average estimation for the population as a whole when investigating food demand in rural China. Given the significant changes in income distribution in rural China, this study provides several important policy implications to alleviate income inequality and poverty, as well as to improve nutrition for lower-income classes.